Unveiling Symbolic Meanings: The Panggih Ceremony in Traditional Java-nese Weddings - Prabowo, Hanta; Patria, Riza; Subianto, Chico (Insan Akademika Publications, 2022)
This research unveils the symbolic depth of the Panggih Ceremony, a central component of traditional Javanese weddings. The ceremony is a living canvas upon which intricate symbols are painted, embodying the core values and beliefs of Javanese culture. Through a detailed exploration of the symbolism inherent in the ceremony's elements, this research offers an illuminating journey into the heart of Javanese traditions. The traditional attire of the bride and groom, marked by the pristine white of the kebaya and the vibrant batik sarong, signifies purity, unity, and balance. The siraman, a ritual of purification, prepares the couple with spiritual and emotional clarity, highlighting the importance of starting their journey with pure hearts. The exchange of gifts, including twin hairpins and a ceremonial dagger, symbolizes promises of love, protection, and support, reinforcing the commitment to mutual well-being. The seserahan, the ceremonial exchange of gifts between families, signifies unity and the merging of households, with each item exchanged carrying specific meaning. The Serimpi dance, celebrated for its grace and harmony, emphasizes coordination and mutual understanding in the marital relationship. The orientation of the couple facing west symbolizes the end of their individual journeys and the commencement of their shared path. The Panggih Ceremony embodies the essence of purity, unity, and balance, celebrating the enduring values and traditions of Javanese culture. It transcends borders and speaks to universal themes, emphasizing the power of tradition and symbolism in commemorating love and unity. This research not only enriches our understanding of the symbolism within cultural ceremonies but also serves as a tribute to the cultural heritage of Javanese society, encapsulating the timeless message that love, unity, and harmony are the cornerstones of a meaningful life journey.